Audit Committee and the Amendments of Quarterly Financial Reports among Malaysian Companies - Ismail, Ku Nor Izah Ku; Abd Rahman, Sharifah Asmawati Syed (Asian Accounting and Auditing Advancement, 2011)
One of the tasks of an audit committee is to ensure the reliability of financial reports. The prevailing amendments of the quarterly reports among companies however question the effectiveness of audit committees. This paper examines the association between audit committee characteristics (independence, expertise, and activities of audit committees) and the amendments of quarterly financial reports of Malaysian companies. Control variables, namely size of the board of directors, size of company, profitability, and auditor are also included in this study. In this study, each of the 63 sampled companies that amended their quarterly reports in 2005 is matched with a company that did not make any amendments. The univariate analysis shows that companies that amend their quarterly reports are likely to be those having audit committees that are less independent, and are comprised of less than two financial experts. They also tend to have a smaller board of directors. Consistent with the univariate test, results of the regression test indicate that companies having audit committees with two or more financial experts are less likely to amend their quarterly reports. Although other variables (except for auditor) appear to have a negative association with amendments, statistically the association is insignificant. This study also observed that most of the amendments are due to oversight, mathematical mistakes, and typographical errors. The findings suggest that to be effective, audit committees should have more than one financial expert. JEL Classification Code: M41, M42, M49